Analysis of the prognostic relevance of sex-steroid hormonal receptor mRNA expression in muscle-invasive urothelial carcinoma of the urinary bladder - Erben, Philipp; Weis, Cleo-Aron Thias (Virchows Archiv, 2019)
Muscle-invasive urothelial carcinoma of the urinary bladder (UCB) often recurs following radical cystectomy (RC). An altered expression of sex-steroid hormone receptors has been associated with oncological outcomes of UCB and may represent therapeutic targets. Here the expression of different hormone receptors was measured on mRNA levels in patients treated by RC and associated with outcomes. Androgen receptor (AR), estrogen receptor 1 (ESR1), and progesterone receptor (PGR) mRNA expression was assessed by quantitative reverse transcription polymerase chain reaction (RT-qPCR) in RC samples of 87 patients with a median age of 66 (39-88) years. Univariate and multivariate analyses were performed to test associations with pathological and clinical characteristics as well as recurrence-free (RFS) and disease-specific survival (DSS). AR mRNA expression was lower in comparison with ESR1 and PGR expression (p < 0.0001). In univariate analysis, high expression levels of AR were associated with reduced RFS (HR 2.8, p = 0.015) and DSS (HR 2.8, p = 0.010). High AR mRNA expression and a positive lymph node status were independent predictors for reduced RFS (HR 2.5, p = 0.0049) and DSS (HR 3.4, p = 0.009). In patients with low AR mRNA expression, an increased ESR1 and PGR mRNA expression were associated with reduced RFS and DSS. High expression levels of AR are significantly associated with adverse outcome in patients with muscle-invasive UCB following RC. ESR1 and PGR expression status can further stratify patients with low AR expression into subgroups with significantly reduced RFS and DSS. Therapeutic targeting of AR may influence outcomes in patients with UCB.
Gesehen am 09.04.2019
Published online: 27 November 2018